A SURVEY ON CRITICAL LITERACY AS A PEDAGOGICAL APPROACH TO TEACHING ENGLISH IN INDONESIA - Gustine, Gin Gin (Indonesian Journal of Applied Linguistics, 2018)
In English-as-a-Foreign-Language (EFL) context, Foreign-Language (EFL) context,critical literacy as an alternative approach to teaching language and literature may be considered as something new, compared to its origin in some English-speaking countries such as Australia or the USA. Teachers wishing to adopt critical literacy stance in their class are often left with little knowledge or experience on what critical literacy is and how to develop this approach in their class. This article discusses the result of a survey involving twenty one English teachers in a teacher education university in Bandung, West Java province, Indonesia, related to their knowledge on critical literacy as an approach to teaching English language. Result of questionnaires followed up by a focus group discussion reveals that although these teachers have been teaching English for approximately five to seven years in different levels of schools, some teachers show lack of knowledge on critical literacy as a methodological approach to teaching English. Finally, this article concludes with suggestions for English teachers to develop a critical literacy-oriented classroom.